2017
DOI: 10.1097/hjh.0000000000001378
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate suppresses angiotensin II-induced hypertension by inhibition of renal (pro)renin receptor and intrarenal renin–angiotensin system

Abstract: These results demonstrate that NaBu exerts an antihypertensive action, likely by suppressing the PRR-mediated intrarenal renin-angiotensin system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 45 publications
4
94
0
Order By: Relevance
“…Previous studies indicated decreased butyrate-producing bacteria in HTN animal models [18,67]. This study, for the first time, demonstrates that butyrate-producing bacteria and butyrate-producing enzymes significant clustered and separated human REF and HBP cohorts (ANOSIM, P =0.024).…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies indicated decreased butyrate-producing bacteria in HTN animal models [18,67]. This study, for the first time, demonstrates that butyrate-producing bacteria and butyrate-producing enzymes significant clustered and separated human REF and HBP cohorts (ANOSIM, P =0.024).…”
Section: Discussionsupporting
confidence: 59%
“…NaBu is generated from butyrate, an important bioactive metabolite produced by gut microbiota. We have previously reported that intrarenal administration of NaBu exerts mild anti‐hypertrophic effect on the hearts in Ang II‐induced hypertensive rats . Consistent with our results, Patel BM and colleagues have recently reported that NaBu has beneficial effect on cardiac hypertrophy in partial abdominal aortic constriction (PAAC) rat model .…”
Section: Discussionsupporting
confidence: 90%
“…NaBu is also reported to work as an inhibitor of histone deacetylases (HDACs) to modulate gene expression and control cardiac hypertrophy in experimental rat model . Our most recent study finds that intrarenal administration of NaBu suppresses Ang II‐induced hypertension by inhibition of renal (pro)renin receptor and exerts anti‐hypertrophic effects on the heart . However, it still remains unknown whether and how systemic administration of NaBu protects against the cardiac hypertrophy induced by Ang II.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fibre‐rich diets or magnesium acetate and oral minocycline supplementation could restore gut microbiota homeostasis, reduce the F/B ratio and attenuate BP levels (Yang, et al , ; Marques, et al , ). In addition, treatment with propionate or butyrate could protect the host from cardiac damage in experimental hypertension models (Wang, et al , ; Bartolomaeus, et al , ). In summary, solid data clearly demonstrate the involvement and therapeutic potential of SCFAs in hypertension.…”
Section: Interactions Between the Gut Microbiota And Cvdmentioning
confidence: 99%